Determinants Analysis of Organizational Citizenship Behaviors - Nadia Motii; Adam Chati (European Scientific Journal, ESJ, 2018)
The purpose of this work is to identify the most representative components and dimensions of the Organizational Citizenship Behaviors within the Moroccan context. The first phase of this paper lies on a theoretical framework defining the individual performance concept, and then we will emphasize the different Organizational Citizenship Behaviors' theories. The method involves an exploratory qualitative inquiry based on directive interviews with executives working in the private companies located in the region of Rabat. The present study reassessed the finding of the existing theories in a purposive sample and in a different context. By identifying the different components of the contextual performance within the Moroccan context we can link several organizational behaviors in the same model, which will pave the way to a confirmatory study. This will allow for more organizationnal consideration of contextual performance and may direct future research on performance management.